The early decades of the Bata Shoe Company in India: From establishment to economic and social integration. (July 2021) - Balaban, Milan; Herman, Jan; Savic´, Dalibor
The study presents a historical and sociological interpretation of the events that marked the gradual integration of the Bata Company into the Indian economy and society from the mid-1920s to the early 1960s. Within this context, in addition to the general economic, political and cultural developments, particular attention has been devoted to the everyday life of Indian and Czech workers in the Bata company town of Batanagar. The study is based on a comparative-historical analysis of available archival sources and a secondary analysis of the relevant academic literature. The results of the research indicate that during this period, Bata was forced to adapt continuously to the cultural specifics of Indian society, that is, the process of its integration into the Indian economy and society had pronounced glocal characteristics.